Prenatal diagnosis of rapidly enlarging choledochal cyst with gastric outlet obstruction. Issue 12 (31st December 2021) - Scalise, P Nina; Yang, Alex; Neumeyer, Corinne; Perez-Atayde, Antonio R; Robinson, Jamie R; Kim, Heung Bae; Cuenca, Alex G
Abstract: Choledochal cysts are congenital malformations of the biliary tract that involve aberrant configurations of the pancreaticobiliary ductal system. The pathology exists on a spectrum from fusiform dilation of the common bile duct to multiple dilations involving the intra- and extrahepatic bile ducts with potential risks of malignant transformation and hepatic fibrosis. Advancements in ultrasound technology have increased the incidence of prenatal diagnosis of choledochal cysts. Here, we present the case of a prenatally diagnosed initially asymptomatic Type I choledochal cyst with rapid progression in the neonatal period to a complete gastric outlet obstruction within the first month of life. We demonstrate the feasibility of cyst resection and reconstruction with Roux-en-Y hepaticojejunostomy in the neonatal age group. Finally, we discuss management of the case based on evolving imaging findings and laboratory evidence of impending liver dysfunction.